Beyond the Anthropocene: emergence, migrations and perspectivism - Cimatti, Felice (Itinerari, 2023)
A critic of the concept of Anthropocene is proposed based on Viveiros de Castro’s notions of “multinaturalism” and “perspectivism”. The idea is that the biopolitical concepts of “emergence” is completely inadequate to understand the intrinsic dynamics of nature. On the contrary, life is intrinsically infectious, that is, life is nothing but a continual process of migration between life forms.